KONSTRUKSI INTEGRAL MENGGUNAKAN FUNGSI SEDERHANA – PADA [A,B] - Aziz, Abdul; Sumanto, YD (MATEMATIKA, 2016)
In this paper, weconstruct the δ –  simple functionusing the δ- fine Perron partition. By this function, we defineintegral, which is called Ho integral.